The Determination Factors of Firm Value by Return on Assets as Mediating Variable - Laksari, Dissa Almi; Oktavia, Vicky (LPPM Institut Pendidikan Nusantara Global, 2024)
This research was carried out to examine the effect between inventory turnover, receivables turnover, and sales growth on firm value with return on assets as a mediating variable. This research uses secondary data sourced from annual reports and IDX statistical data. The population of this research included 25 agricultural sectors. The sample selection method used a purposive sampling method with specific qualifications so that 120 data were obtained from 12 firms. The findings of this research are that receivables turnover and sales growth influence return on assets. Inventory turnover and receivables turnover do not affect firm value. However, there is a positive and significant influence of sales growth and return on assets on firm value. In addition, return on assets can mediate receivables turnover on firm value.